Dinamika Kelompok Pendidikan di Lembaga Pondok Pesantren Jaisyul Quran Nagreg - Abdul Haris (Tadbir: Jurnal Manajemen Pendidikan Islam, 2021)
ABSTRACT The study of this paper is to describe the main discussion of group dynamics in educational institutions. The group dynamics can be used as a management tool for the progress of the Islamic Boarding School Jaisyul Quran Nagreg. The method used is descriptive quantitative with a population of 41 teachers and leaders. Data retrieval using a Likert scale instrument that has been tested for validity and reliability. The result obtained from this study are the dynamics of the Pondok Jaisyul Quran group seen from eight aspects showing a good category. Aspect Goal group achieved a relative score of 73%. Aspects of group stucture 73%. Task and roles of groups 73%. Aspect of group coaching 71%. Group cohesiveness aspect 69%. Aspects of group atmosphere 71%. Aspect group pressure 70%. The aspect of group effectiveness is 68%.